ADAPTATION OF PARENTS' ROLE FUNCTIONS POST DISASTER WITH BALANCED NUTRITION NEEDS FULFILLMENT OF TOGETHER - Putra, Ageng Abdi; Rosyidi, Muhammad; Astuti, Febriati; Ilmi, Nurul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Background : In 2018, Lombok had earthquake for about 3 weeks which killed a lot of victims, disaster and make people become refugees. Disaster makes stress and trauma for victims that need to adapt with new environment to fulfill their basic needs especially balanced nutrition. This research is aimed at identifying the correlation between the pattern of adaptation of parent’s post disaster role and the fulfillment of balanced nutrition of toddlers.Method : This research is designed as correlational study with Cross-sectional approach. The samples were 89 respondents selected through proportional random sampling technique. The data were collected using 2 types of questionnaires distributes to women with toddlers.Result : The research showed that of 89 respondents, 63 respondents (70.2%) had the adaptive role, 26 of them (29.2%) had ineffective role. In relation to balanced nutrition, it is 67 respondents (75.2%) that fulfill the balanced nutrition. Statistic test of spearmen rank’s correlation showed that (rho) value < 0.05 (0.00<0.05) which means that Ha is accepted. The correlation value is 0.584 meaning that there is strong and positive correlation.Conclution : It is inferred that there is correlation between the pattern of adaptation of parent’s post disaster role and the fulfillment of balanced nutrition of toddlers in Jenggala.